Pemanfaatan Fasilitas Kesehatan dan Biaya Pengeluaran bagi Akseptor KB dalam Mendapatkan Layanan Kontrasepsi di Jawa Barat: Utilization of Health Facilities and Expenditures for Family Planning Acceptors in Getting Contraceptive Services in West Java - Atriany Nilam Sari; Ari Indra Susanti; Noormarina Indraswari (Jurnal Bidan Cerdas, 2022)
Introduction: The family planning program is a promotive and preventive service, including counseling and the use of non-long-term contraceptive methods and long-term contraceptive methods (MKJP). However, there is a decrease in the use of Intrauterine Contraceptive Devices caused by health service factors, namely procedures, health workers, costs, and infrastructure related to the selection of contraceptives. Purpose: This study describe the utilization of health facilities and the costs of spent by family planning acceptors in obtaining contraceptive services in West Java. Methods: This study used secondary data from the 2019 SKAP data with 5,430 modern family planning acceptors. Results: Most respondents, who used sterilization, IUDs, implants, and injections, received the services from private midwives (54.54%) and village midwives (24.25%). Meanwhile, for users of contraceptive pills and male condoms, the majority of respondents received these contraceptives from pharmacies/drug stores (64.9%). For non-MKJP users, 95.92% of them without insurance coverage. While 76,52% MKJP users also used the services without being covered by insurance. Conclusion: Utilization of health facilities with the cost of birth control services borne by BPJS or Jamkesda is still very low. Thus, promote health related to the use of MKJP and the use of BPJS need to be improved.     ABSTRAK Pendahuluan: Program KB merupakan pelayanan promotif dan preventif, mencakup konseling dan penggunaan kontrasepsi non Metode Kontrasepsi Jangka Panjang (Non MKJP) dan Metode Kontrasepsi Jangka Panjang (MKJP). Terdapat penurunan pemakaian Alat Kontrasepsi Dalam Rahim (AKDR) disebabkan oleh prosedur, petugas, biaya, dan sarana prasarana yang berhubungan pemilihan alat kontrasepsi. Tujuan: Penelitian ini bertujuan untuk mengetahui pemanfaatan fasilitas kesehatan dan biaya pengeluaran bagi akseptor KB dalam mendapatkan layanan kontrasepsi di Jawa Barat. Metode: Penelitian ini menggunakan pendekatan potong lintang dengan data sekunder dari data Survei  Kuesioner Akuntabilitas Penelitian (SKAP) tahun 2019. Subjek penelitiannya adalah akseptor KB modern sebanyak 5.430 orang. Hasil: Pengguna alat/metode KB, (IUD, implan, dan suntik) paling banyak mendapatkan pelayanan KB dari praktik bidan swasta (54,54%) dan bidan desa (24,25%). Sedangkan untuk pengguna pil KB dan kondom pria paling banyak mendapatkan alat KB tersebut dari apotik/toko obat (64,9%). Pada bukan pengguna MKJP, sebanyak 95,92% tidak menggunakan asuransi dalam mendapatkan pelayanan KB. Sedangkan pengguna MKJP 76,52% responden juga tidak menggunakan asuransi. Simpulan: Pemanfaatan fasilitas kesehatan dengan biaya pelayanan KB yang ditanggung BPJS atau Jamkesda masih sangat rendah. Dengan demikian, upaya promosi kesehatan terkait penggunaan layanan MKJP dan pemanfaatan BPJS perlu ditingkatkan.